Beliefs about Racial Discrimination and Support for Pro-Black Policies - Ingar Haaland; Christopher Roth (Center for Economic Studies and ifo Institute (CESifo), 2019)
We examine whether information about racial discrimination causally affects support for pro-black policies. Using representative samples of Americans, we elicit quantitative and incentivized beliefs about the extent of hiring discrimination against blacks. Relative to Republicans, Democrats think that blacks have to send out 47 percent more resumes than whites to receive a callback. An information treatment substantially narrows Republican–Democrat differences in beliefs, but fails to narrow differences in political behavior. Overall, the results demonstrate that correcting biases in beliefs about the extent of racial discrimination is not sufficient to reduce political polarization in support for pro-black policies.
Keywords: 330; racial discrimination; beliefs; pro-black policies; policy preferences